Prevalence of candidemia in intensive care units (European Journal of Health Research, 2017)
There are many risk factors for the development of candidemia common to the majority of patients in intensive care units. Candida is currently considered to be the fourth most common source of nosocomial blood stream infections (BSI) in these units, causing significant morbidity and mortality in critical patients. This prospective work presents the results of a study on the epidemiology of Candida infection, as well as contributing risk factors. A simple random sample of 75 patients in the ICU of a general hospital in the Andalusian region were monitored from January to July 2015. Exclusion criteria were: short-term hospitalisation and minimally invasive procedures. Data was collected during direct patient care, monitoring patient evolution and blood culture collection every 2-3 days, or on signs of possible colonisation. The results showed a 21.3% prevalence of candidemia, with 66,7% due to C. albicans pathogen. Among risk factors for development were 96% nosocomial BSI and 88% antibiotic use. Epidemiological information and knowledge of risk factors can reduce the incidence, along with hygiene measures, optimisation of care, early diagnosis and specific antifungal treatment.
Keywords: Antifungal; candidemia; risk factor's; morbidity and mortality